Hubungan tingkat pengetahuan dengan kesiapan masyarakat dalam melakukan pertolongan pertama korban kecelakaan lalu lintas pada Mahasiswa Keperawatan di STIKES Nani Hasanuddin - Kartika Sari Wijayaningsih (NHM PRESS, 2023)
Accident is an emergency condition that is life threatening and requires immediate help. First aid in an accident is a treatment for accident victims before being treated by medical personnel with the aim of preventing victims from more severe injuries. Nursing students are not only required to have basic knowledge and skills in nursing practice, but also have the ability to respond to emergency conditions. Analyzing the relationship between the level of knowledge and readiness in performing first aid for accident victims in STIKes Nani Hasanuddin nursing students. The research is quantitative research with corelational analytic design. The design is cross sectional. The sample was 38 respondents with total sampling technique. The data was processed with SPSS 24 for windows, to analyze univariate and bivariate data with the sommers’D test. Results: Most of the respondents have a good level of knowledge 89,5 and readiness which is included in the ready category 86,8%. The result of the sommers’D test show that there is a relationship between the level of knowledge and readiness in performing first aid for accident victims in nursing students (p-value=0,017, r=0,971). Conclusion: There is a significant relationship between the level of knowledge and readiness in performing first aid for accident victims in nursing students of STIKes Nani Hasanuddin. If the level of first aid knowledge of accident victims is good, then the readiness to caryy out first aid will also be good or ready.